Zoneamento ambiental do município de Monteiro-PB - Maranhão, Karinna Ugulino de Araújo (2014)
The objective is to evaluate the environmental fragility and guidelines for environmental zoning (EZ) using geospatial analyses techniques in the Monteiro County, Paraíba State. The purpose of this study was to evaluate two different environmental fragility methodologies to use the results to develop environmental zone classes within Brazilian semiarid region. The two methodologies used in this study were: (a) original purpose developed by Crepani et. al. (2008) and adapted to the local reality, in which it was analyzed the vulnerability to soil loss, its use and occupation, and the Permanent Preservation Areas (PPAs); (b) adopted purpose of Crepani et. al. (2008), that instead of using the map of soil loss vulnerability, it was used the estimation of soil loss achieved from the Universal Soil Loss Equation (USLE). The map of soil loss vulnerability was achieved by algebra of maps related to the following themes: Geology, Geomorphology, Pedology, Land Use Cover, and Climatology. The estimative map of soil losses, using USLE, was achieved from the factors of rainfall erosivity, soil erodibility, topographic and management, and conservation practices. As a result, two EZ maps were achieved. In both cases were identified ten types of indicated use, having one of them presented a higher percentage of Environmental Control area, which demands maintenance of both the existent vegetal cover and the quality of hydric sources; while another map has presented a higher percentage of Priority Preservation Area, which presents areas covered by vegetation of dense and preserved forest, but with high erosion degree. This research not only shows the city areas of higher environmental vulnerability, but also proves the importance of EZ to the control of soil use and occupation in an orderly and planned way. It is, then, government duty to elaborate, based on this study, its law to ordainment of territory. From this research it is possible to deepen the studies to create the Ecological-Economic Zoning (EEZ), which is concerned not only with the preservation, rehabilitation and recovery of environmental quality, but also with the social and economic development.